Pengetahuan Pajak, Persepsi Mahasiswa, Minat Mahasiswa Dalam Berkarir di bidang Perpajakan - Icha Novianingdyah (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: The purpose of this research is to examine knowledge tax, perception student to interest student in career in the field tax moderated by principle independence.Method: In this study, the researcher took a sample from study program student Accounting Class of 2018 and 2019 University Sarjanawiyata Tamansiswa Yogyakarta. Total sample as many as 103 students. Finding: Knowledge tax no take effect to interest student in career in the field tax, perception student take effect positive to interest student in career in the field tax, basic independence strengthen influence knowledge tax to interest student in career in the field tax, the principle independence no capable be a moderating variable perception student to interest student in career in the field tax.Novelty: The motivation variable is updated into tax knowledge aimed at accounting students as candidates for a career in taxation and independence as a moderating variable.